Sedimentary phosphorus in contrasting, shallow New Zealand lakes and its effect on water quality. Issue 4 (2nd October 2021) - Waters, Sean; Verburg, Piet; Schallenberg, Marc; Kelly, David
ABSTRACT: The eutrophication of lake ecosystems due to anthropogenic activities has impacted lakes worldwide and shallow lakes are particularly vulnerable. The retention of phosphorus (P) in lake sediments and its subsequent release to the water column is often a key factor in degraded water quality, algal blooms and delayed responses to lake restoration efforts. Despite this link between sedimentary P and poor ecosystem outcomes, a limited amount of research has been conducted on P dynamics in New Zealand's lakes. In this study, sediments in six shallow lakes across the country were analysed for geochemistry and P fractionation. Total sedimentary P content varied widely and was related to inflow concentrations and hydrological retention times. The P binding capacity of the sediments was related to iron (Fe) and aluminium (Al) concentrations, while the Fe:P ratio was correlated to the release of P under anoxic conditions. P fractions and release rates were poorly correlated with traditional water quality parameters, however the mobile-PSL and reducible-P fractions were strongly correlated with the frequency of summertime algal blooms. This relationship may provide an indicator to assess harmful algal bloom frequency in unmonitored lakes, and a valuable tool to assess internal loading risk and inform lake restoration methods.